The effect of psychosomatic disorders (psycho-physical) and its relationship to job creativity among workers in the Ministry of Youth and Sports (Journal of the College of Basic Education, 2022)
The study aimed to prepare measures of psychosomatic disorders (psycho-physical and job creativity) among workers in the Ministry of Youth and Sports. The scientific bases for this scale were conducted. The researcher used the descriptive approach in a survey method with correlative relations to suit the nature of the study. The research community included the employees of the Ministry of Youth and Sports represented by the Department (Sports Medicine) in Iraq, who numbered (110), and the research sample was chosen by random method, as the application sample reached ( 110) employees, and the scientific bases were extracted, and the researcher concluded (for the psychosomatic disorders scale (psycho-physical) for workers in the Ministry of Youth and Sports, and the employees enjoyed an average level of job creativity.